Традиційні сюжети: архетип дерева - Гаврилюк, Н. (Літературознавчі обрії. Праці молодих учених, 2010)
Two poems from the selection by Maryna Kononenko «Between the crown and roots» are considered in the article. A biblical plot about the Tree of life and the Tree of cognition can be traced in these texts. The study deals with the actualization of cultural and existential tree archetype. Maryna Kononenko tries to measure human existence referring to tree varieties (cherry tree, apple tree).